The Oral Delivery System of Modified GLP-1 by Probiotics for T2DM - Qing Wang; Haixin Guo; Wenwei Mao; Xiuping Qian; Yangang Liu (MDPI AG, 2023)
The glucagon-like peptide-1 (GLP-1) is a peptide with incretin activity and plays an important role in glycemic control as well as the improvement of insulin resistance in type 2 diabetes mellitus (T2DM). However, the short half-life of the native GLP-1 in circulation poses difficulties for clinical practice. To improve the proteolytic stability and delivery properties of GLP-1, a protease-resistant modified GLP-1 (mGLP-1) was constructed with added arginine to ensure the structural integrity of the released mGLP-1 in vivo. The model probiotic Lactobacillus plantarum WCFS1 was chosen as the oral delivery vehicle with controllable endogenous genetic tools driven for mGLP-1 secretory constitutive expression. The feasibility of our design was explored in db/db mice which showed an improvement in diabetic symptoms related to decreased pancreatic glucagon, elevated pancreatic β-cell proportion, and increased insulin sensitivity. In conclusion, this study provides a novel strategy for the oral delivery of mGLP-1 and further probiotic transformation.